Public Attitudes Toward New Prisons in New Zealand and Deficit Narratives: A Quantitative Survey - Norris, Adele N. (International criminal justice review, 2019)
The imprisonment rate in New Zealand ranks seventh among the Organisation for Economic Co-operation and Development (OECD). Yet the imprisonment of Indigenous people is on par with the United States, which has the world’s highest incarceration rate. Almost 70% of the prison population in New Zealand is comprised of people racialized as non-White. In 2016, the National Government proposed to spend $2.5 billion over a 5-year period to build new prisons (1,500 prison beds) to accommodate a growing prison population. This study assessed public attitudes toward the need for more prisons and the equity of treatment of individuals within the criminal justice system. Findings from a 2016 and 2017 quantitative survey of 5,000 respondents each year revealed that roughly half of the respondents believed the proposed spending for new prisons to be extremely to somewhat necessary. A large proportion of respondents also believed Māori and Pākehā, if convicted of the same crime, are treated similarly within the criminal justice system. New Zealand scholars have critiqued news media coverage of contentious sociopolitical issues, such as crime and prisons, for employing tactics that have worked to construct a morally and culturally deficit “Other” while normalizing whiteness, rendering it invisible and raceless. This article concludes that this process masks racial disparities of individuals located within the criminal justice system and preserves the ideal that prisons are a normal function of the social landscape.